Hubungan Pemberian Asi Eksklusif Dan Perilaku Ibu Dalam Cuci Tangan Pakai Sabun Dengan Kejadian Penyakit Diare Pada Bayi Usia 6-12 Bulan diWilayah Kerja Puskesmas Banyudono IIKabupaten Boyolali - Suryaningtyas, Yuni; , Bejo Raharjo, SKM, M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2016)
The number of cases of diarrhea treated at the health center Banyudono II Boyolali, Central Java in 2015 that is equal to 624 votes (78.96%) and to the number of incident cases of diarrhea in infants treated Puskesmas Banyudono II in 2015 as many as 74 infants. Babies who are exclusively breastfed in 2015 only about 79 infants the number of babies aged 6 months as many as 127. This study aimed to analyze the relationship between the exclusive breast feedingmother and maternal behavior in handwashing with soap to incidence of diarrhea in infants aged 6-12 months working area Banyudono II Boyolali district health centers. This type of research is observational with cross sectional approach. The population in this study are all mothers with babies aged 6-12 months a number of 127 people in Puskesmas Banyudono II Boyolali. Selection of a sample of 106 infants using proportionate random sampling technique, using statistical test Chi Square. The results showed that there was a relationship between exclusive breastfeeding (p = 0.004) and the relationship between the mother's behavior in handwashing with soap (p = 0.003) and the incidence of diarrheal disease in PuskesmasBanyudono II Boyolali.